Muscle-specific deletion of SOCS3 increases the early inflammatory response but does not affect regeneration after myotoxic injury. Issue 1 (December 2016) - Swiderski, Kristy; Thakur, Savant; Naim, Timur; Trieu, Jennifer; Chee, Annabel; Stapleton, David; Koopman, René; Lynch, Gordon
Abstract Background Muscles of old animals are injured more easily and regenerate poorly, attributed in part to increased levels of circulating pro-inflammatory cytokines. The Janus kinase/signal transducers and activators of transcription (JAK/STAT) signaling cascade is a key mediator of inflammatory cytokine action, and signaling via this pathway is increased in muscles with aging. As a negative regulator of JAK/STAT signaling, a key mediator of myogenic proliferation and differentiation, altered expression of suppressor of cytokine signaling (SOCS3) is likely to have important consequences for muscle regeneration. To model this scenario, we investigated the effect of SOCS3 deletion within mature muscle fibers on injury and repair. We tested the hypothesis that reduced SOCS3 function would alter the inflammatory response and impair muscle regeneration after myotoxic injury. Methods Mice with a specific deletion of SOCS3 within mature skeletal muscle fibers were used to assess the effect of SOCS3 deletion on muscle injury and repair. Twelve-week-old or 24-month-old SOCS3 muscle-specific knockout (SOCS3 MKO) mice and littermate controls were either left uninjured or injured with a single injection of notexin (10 μg/ml) into the right tibialis anterior (TA) muscle. At 1, 2, 3, 5, 7, or 14 days post-injury, the right TA muscle was excised and subjected to histological, western immunoblotting, and gene expression analyses. Force production and fatigue were assessed in uninjured muscles and at 7 days post-notexin injury. Results In uninjured muscles, SOCS3 deletion decreased force production during fatigue but had no effect on the gross or histological appearance of the TA muscles. After notexin injury, deletion of SOCS3 increased STAT3 phosphorylation at day 1 and increased the mRNA expression of the inflammatory cytokineTNF-α, and the inflammatory cell markersF4/80 andCD68 at day 2. Gene expression analysis of the regeneration markersPax7, MyoD, andMyogenin indicated SOCS3 deletion had no effect on the progression of muscle repair after notexin injury. Inflammation and regeneration were also unchanged in the muscles of 24-month-old SOCS3 MKO mice compared with control. Conclusions Loss of SOCS3 expression in mature muscle fibers increased the inflammatory response to myotoxic injury but did not impair muscle regeneration in either adult or old mice. Therefore, reduced SOCS3 expression in muscle fibers is unlikely to underlie impaired muscle regeneration. Further investigation into the role of SOCS3 in other cell types involved in muscle repair is warranted.